2021
DOI: 10.1590/1518-8345.4759.3414
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up care for premature children: the repercussions of the COVID-19 pandemic

Abstract: Objective: to analyze elements of the follow-up care provided to premature children amidst the COVID-19 pandemic. Method: qualitative study from the perspective of philosophical hermeneutics, interpreting experiences with childcare provided at home. Twelve mothers and 14 children aged two years old were interviewed online via a text messaging application. Data were analyzed by interpreting meanings. Results: weaknesses stood out in the follow-up care provided to children such as gaps of communication, lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
8
Order By: Relevance
“…Entre os fatores listados pela literatura que mais contribuíram para o aumento da violência masculina contra a mulher no Brasil em tempos de pandemia, Silva et al 46 identificaram: o isolamento social com os parceiros; o consumo de álcool e demais drogas pelos parceiros; a pressão da crise econômica sobre o casal; a sobrecarga feminina; e o enfraquecimento da rede de apoio da mulher. Alguns estudos adicionaram o medo de adoecer e a incerteza da conjuntura entre esses fatores 43, 44 .…”
Section: Violência Contra a Mulherunclassified
See 1 more Smart Citation
“…Entre os fatores listados pela literatura que mais contribuíram para o aumento da violência masculina contra a mulher no Brasil em tempos de pandemia, Silva et al 46 identificaram: o isolamento social com os parceiros; o consumo de álcool e demais drogas pelos parceiros; a pressão da crise econômica sobre o casal; a sobrecarga feminina; e o enfraquecimento da rede de apoio da mulher. Alguns estudos adicionaram o medo de adoecer e a incerteza da conjuntura entre esses fatores 43, 44 .…”
Section: Violência Contra a Mulherunclassified
“…Todos os autores aqui revisados buscaram identificar os desafios da VCM e enfatizaram a necessidade de ampliar a rede de apoio/ cuidado e de prover alternativas e meios para a proteção/acolhimento das mulheres 42-44, 46 . Entre os desafios mais relevantes elencados, figuram: a redução brusca da renda familiar; o aumento do uso abusivo de álcool e outras drogas por parte dos parceiros; a qualificação profissional para a abordagem interseccional da rede de apoio; e o trabalho com os homens agressores.…”
Section: Violência Contra a Mulherunclassified
“…Silva et al 46 identified the factors listed in the literature that contributed the most to increasing male violence against women in Brazil in times of a pandemic, as follows: social isolation with partners; consumption of alcohol and other drugs by partners; the pressure of the economic crisis on the couple; female overload; and the weakening women's support network. Some studies added the fear of getting sick and the uncertain situation among these factors 43,44 .…”
Section: Violence Against Womenmentioning
confidence: 99%
“…All the authors reviewed here sought to identify the challenges of VAW and emphasized the need to expand the support/care network and to provide alternatives and means for the protection/reception of women 42-44, 46 . The sudden decline in household income, increased abuse of alcohol and other drugs by partners, the professional qualification for the intersectional approach to the support network, and working with male physical abusers listed among the most relevant challenges.…”
Section: Violence Against Womenmentioning
confidence: 99%
“…A pandemia da Covid-19 trouxe inúmeras repercussões para a assistência prestada às crianças nascidas prematuras, como observado em estudos nacionais e internacionais que identificaram interrupção no acompanhamento de lactentes prematuros após a alta hospitalar, devido à paralização momentânea dos serviços de seguimento, com consequência para a descontinuidade da atenção à saúde prestada à essa população 10,11 .…”
Section: Introductionunclassified